Hubungan Dukungan Keluarga dengan Tingkat Depresi pada Pasien yang Menjalani Terapi Hemodialisa di Unit Hemodialisa Rumah Sakit Tentara Dr Soedjono Magelang - Anggraeni, Kartika Nurmalia; Sarwono, Bambang; Sunarmi, (Jurnal Keperawatan Soedirman, 2017)
Hemodialysis can change the physical aspect and the psychological aspects of the patient's life and it can trigger stressor for patients that finally lead to depression. Therefore, family support is very important for patients undergoing hemodialysis. The purpose of this study was to determine the relationship between family support and the level depression of patients with hemodialysis therapy in hemodialysis units at RST dr. Soedjono Magelang. Type of this research is a descriptive correlation with a cross-sectional design. there are 46 respondents as samples and the techniques sampling used accidental sampling. Data collected by using a family support questionnaire and Hamilton Depression Rating Scale (HDRS) questionnaire. Data analysis used Kendall tau analysis. The results obtained p-value = 0.000 with significance at p